Dry-mixed thin anti-crack waterproof plastering mortar and preparation method thereof

By using a nano-clay-alginate composite water-retaining system and gradient fiber distribution, combined with silane-modified carbon fiber and MgO-type expansion agent, the problems of low water retention, weak interfacial bonding and incomplete crack control of dry-mixed thin-film crack-resistant waterproof plastering mortar are solved. It is suitable for high-rise building exterior wall insulation systems and achieves high-strength and crack-free waterproof effect.

CN121248201APending Publication Date: 2026-01-02CHANGXING BEISI DEBANG BUILDING MATERIALS TECH CO LTD

Patent Information

Application Number
CN202511506930.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-21
Publication Date
2026-01-02

AI Technical Summary

Technical Problem

Existing dry-mixed thin-film crack-resistant and waterproof plastering mortars have limitations in terms of water retention, interfacial bonding strength, and crack control, especially in high-rise building exterior walls, where they cannot effectively address the interfacial bonding problem in high-stress areas.

Method used

Mortar is prepared using a nano-clay-alginate composite water-retaining system, silane-modified carbon fiber, redispersible latex powder, and MgO-type expansion agent through a full-aqueous phase process. Combined with gradient fiber distribution and nanomaterial reinforcement, a multi-scale fiber network is formed, which enhances interfacial bonding strength and reduces the risk of cracking.

Benefits of technology

It achieves high water retention rate (≥99.0%), high interfacial bond strength (≥0.25 MPa) and cracking index of 0 mm, significantly improving the overall performance and durability of the exterior wall insulation system for high-rise buildings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and particularly relates to dry-mixed thin anti-crack waterproof plastering mortar and a preparation method thereof.The dry-mixed thin anti-crack waterproof plastering mortar is prepared from, by weight, 120-150 parts of cement; 550 to 650 parts of quartz sand; the silane modified carbon fibers are carbon fibers subjected to gamma-aminopropyltriethoxysilane surface grafting treatment, and the grafting rate is greater than or equal to 90%; 5-11 parts of a nano clay-alginate composite water retention system, the composite water retention system is formed by crosslinking 1-3 parts of sodium alginate and 4-8 parts of nano attapulgite to form a hydrogel network, and the hydrogel network is coated with the nano attapulgite; 2-4 parts of redispersible latex powder; 0.1 to 0.5 part of hydroxypropyl methyl cellulose ether; and 5-10 parts of an expanding agent. According to the technical scheme, the problems that in the prior art, water retention is insufficient, interface bonding is weak, and cracking control is not thorough are solved, and the method is suitable for high-rise building outer wall heat preservation system protection layers.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of building materials, in particular to a dry-mixed thin anti-cracking waterproof plastering mortar and a preparation method thereof. BACKGROUND

[0002] The dry-mixed thin anti-cracking waterproof plastering mortar is composed of ordinary Portland cement, dry fine aggregate, mineral admixture and functional additives, and is prepared into a dry mixture by mixing in proportion, and is mixed with water in proportion for use. The dry-mixed thin anti-cracking waterproof plastering mortar is divided into two types according to the use, and the type II is used for an anti-cracking protective layer on the surface of a thermal insulation layer, which is combined with an alkali-resistant glass fiber mesh to play the roles of anti-cracking and waterproofing, and the average thickness is not greater than 8 mm.

[0003] The existing type II dry-mixed thin anti-cracking plastering mortar has the following defects: 1. It only relies on cellulose ether, and the water retention rate is not high; 2. It is not optimized for the thermal insulation board substrate, the tensile bonding strength test substrate is not fixed, and it cannot be ensured that the damage occurs in the thermal insulation layer; 3. The anti-cracking additive relies on pore filling, and the cracking index is at least 0.15 mm; Therefore, there is an urgent need for an environmentally friendly type II mortar that meets the requirements of high water retention, high interfacial bonding and anti-cracking. SUMMARY

[0004] In order to solve the problems in the related art, the present application provides a dry-mixed thin anti-cracking waterproof plastering mortar and a preparation method thereof. The mortar is prepared by a whole water phase process, and the main raw materials are cement, quartz sand, silane modified carbon fiber, nano clay-alginate composite water retention system, redispersible latex powder, hydroxypropyl methyl cellulose ether and MgO type expanding agent. The water retention rate is greater than or equal to 99.0%, the original tensile bonding strength with the EPS / XPS thermal insulation board is greater than or equal to 0.25 MPa after 14 days, and the damage occurs in the thermal insulation layer. The cracking index is 0 mm. The technical solution of the present application solves the problems of insufficient water retention, weak interfacial bonding and incomplete cracking control in the prior art, and is suitable for the protective layer of the thermal insulation system of high-rise buildings.

[0005] In the first aspect, the present application provides a dry-mixed thin anti-cracking waterproof plastering mortar, which contains, by weight: cement 120-150 parts; quartz sand 550-650 parts; silane modified carbon fiber 0.8-2.4 parts, the silane modified carbon fiber is carbon fiber treated by surface grafting of γ-aminopropyl triethoxysilane, and the grafting rate is greater than or equal to 90%; Nanoclay-alginate composite water retention system 5-11 parts, which is composed of sodium alginate cross-linked with calcium ions to form a hydrogel network and coated with nanometer attapulgite, wherein sodium alginate 1-3 parts, nanometer attapulgite 4-8 parts; Redispersible latex powder 2-4 parts; Hydroxypropyl methylcellulose ether 0.1-0.5 parts; Expanding agent 5-10 parts.

[0006] In the present disclosure, quartz sand (40-70 mesh) is used as the basic aggregate component, together with cement and nanoclay-alginate composite to form the main structure of the mortar. The selection of 40-70 mesh quartz sand can provide appropriate particle size distribution, ensuring that the mortar has good workability and strength. The quartz sand in this particle size range can form a close skeleton structure with the cement paste, reducing porosity and improving the density and strength of the mortar. At the same time, appropriate particle size distribution is also beneficial to improve the water retention and crack resistance of the mortar. In practical applications, the amount and particle size distribution of quartz sand can be adjusted according to different construction requirements. For example, for applications requiring higher strength, 620-650 parts of quartz sand can be considered, and the proportion of fine particle size (60-70 mesh) can be appropriately increased to improve the density and strength of the mortar.

[0007] In the present disclosure, sodium alginate (ALG) is cross-linked with calcium ions to form a three-dimensional hydrogel network, with a water locking rate as high as 99.8%, effectively preventing rapid water loss. Nanometer attapulgite (AT) has a large specific surface area and a layered structure, which can adsorb free water and delay the release of hydration heat, further improving the water retention performance. The AT nanosheet layers are inserted into the cement pores, forming a physical barrier to block the expansion of microcracks, achieving an opening crack index of 0 mm.

[0008] In the present disclosure, γ-aminopropyl triethoxysilane (KH550) forms a grafting layer on the surface of carbon fiber, and its amino group can react with the ester bond on the surface of the insulation board (EPS / XPS). This chemical bonding significantly enhances the interfacial bonding force between the fiber and the insulation board, ensuring that the bonding strength is ≥0.20 MPa and the failure occurs in the insulation layer.

[0009] The addition amount of silane modified carbon fiber is 0.8-2.4 parts, preferably 0.8-1.5 parts. Further preferably, it is 1.8-2.4 parts. Specifically, in the high stress areas around the top, corners and openings of the building, the amount of silane modified carbon fiber is increased to 1.8-2.4 parts, and 3 mm, 6 mm, 9 mm carbon fibers are introduced in a mass ratio of 1:2:1 to form a multi-scale fiber network. Preferably, 0.5-1.5 wt% of nano-silica with a particle size of 10-50 nm is additionally added in the high stress area to strengthen the interface transition zone.

[0010] A special technical challenge arises when applying dry-mix thin anti-cracking waterproof plaster mortar in high-rise building external wall insulation systems. Due to the increased building height, the external walls face stronger wind pressure and temperature changes, leading to increased interfacial stress between the plaster layer and the insulation board. This stress concentration phenomenon is more pronounced at the top and corner areas of the building. Although silane-modified carbon fibers improve the interfacial bonding strength, local detachment or cracking may still occur in these high-stress areas. The main reasons for this problem are the uneven distribution of wind loads and thermal stresses specific to high-rise buildings, as well as the stress concentration effects caused by the building's geometry. Conventional uniform reinforcement methods are ineffective in dealing with this local high-stress condition, so further optimization is needed to address the specific needs of high-rise buildings.

[0011] To solve the interfacial bonding problem in the local high-stress areas of high-rise building external wall insulation systems, the amount of silane-modified carbon fibers is increased, and a gradient distribution of fiber reinforcement structure is introduced into the mortar to specifically strengthen the high-stress areas.

[0012] The specific implementation method is as follows: 1. Fiber gradient distribution design: According to the building height and geometry, the external wall is divided into different stress areas. The amount of silane-modified carbon fibers is increased in high-stress areas (such as the top, corners, and around openings) to form a gradient distribution. For example, the amount of carbon fibers remains unchanged at 0.8-1.5 parts, preferably 1.2 parts in standard areas, while it is increased to 1.8-2.4 parts in high-stress areas.

[0013] 2. Multi-scale fiber composite: Different lengths of carbon fibers, such as 3mm, 6mm, and 9mm, are introduced in high-stress areas. This multi-scale fiber network can more effectively disperse stress and prevent crack propagation at different scales.

[0014] 3. Local reinforcement of nanomaterials: The addition of nano-silica is also increased in high-stress areas, from 0.5% to 1-1.5%. Nano-silica can fill the micro-pores between cement hydration products, enhance the structure of the interfacial transition zone, and improve the bonding strength and durability of the local area.

[0015] The working principle of this gradient reinforcement optimization scheme is to form a more robust interfacial structure in high-stress areas by precisely controlling the amount, size of fibers, and local addition of nano-silica materials. The multi-scale fiber network provides a comprehensive stress transfer and dispersion mechanism. The addition of nanomaterials further optimizes the microstructure, improving the bonding strength and durability of the interface.

[0016] Through this optimization scheme, the interfacial bonding problem in the local high-stress areas of high-rise building external wall insulation systems can be effectively solved, significantly improving the overall performance and durability of the system.

[0017] In the present disclosure, the length of the silane-modified carbon fiber is 3-9 mm, preferably 6 mm.

[0018] In the present disclosure, the addition of MgO type expanding agent can compensate for the shrinkage of the mortar during hardening, further reducing the risk of cracking. MgO will slowly generate Mg(OH)2 during hydration, with a volume expansion of about 120%. This micro-expansion effect can offset the shrinkage stress during cement hydration, thereby reducing the formation of micro-cracks. In practical applications, the amount of expanding agent can be adjusted according to the specific formulation, usually between 5-10 parts. For example, during winter construction, the hydration speed of MgO will be slowed down due to low temperature, so the amount can be appropriately increased to 8-9 parts to ensure sufficient expansion effect.

[0019] In the present disclosure, the redispersible latex powder (VAE) forms a flexible polymer film in the mortar, enhancing the toughness and deformation ability of the mortar. This flexible film can absorb part of the stress, reducing the generation of micro-cracks. At the same time, VAE can also improve the adhesion of the mortar to the base layer, especially at the interface with the insulation board, forming a synergistic effect with the silane-modified carbon fiber, further improving the overall adhesion strength. In practical applications, the amount can be adjusted according to different environmental conditions and performance requirements. For example, when constructing in a high humidity environment, the amount of VAE can be slightly increased to 3.5-4.0 parts to improve the waterproof performance and durability of the mortar.

[0020] In the present disclosure, hydroxypropyl methylcellulose ether (HPMC) has excellent water retention and thickening effect, which can assist the main water retention system to maintain the workability of the mortar. It can form a water-soluble gel to slow down water evaporation and prolong the operable time of the mortar. At the same time, HPMC can also improve the viscosity and thixotropy of the mortar, which is beneficial to uniform coating and reducing sagging during construction. In practical applications, the amount of HPMC can be adjusted slightly according to the environmental temperature and humidity. For example, in hot and dry summer, the amount of HPMC can be appropriately increased to 0.4-0.5 parts to enhance the water retention effect and prevent cracking caused by rapid water loss of the mortar.

[0021] According to the embodiment of the present disclosure, the nanoclay-alginate composite water retention system is prepared by the following steps: Disperse nanometer attapulgite in deionized water to form a 5-10 wt% suspension; Add sodium alginate under the condition of 25±5℃ and 200-400 rpm stirring, so that the concentration of sodium alginate is 1-3wt%; Slowly add 2-3 wt% CaCl2 solution for ion crosslinking; After crosslinking, spray drying to obtain microspheres with a particle size of 50-100 μm.

[0022] According to the embodiment of the present disclosure, the preparation method of the silane-modified carbon fiber comprises: The carbon fiber is placed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 3:1 for acid washing at 60-80°C for 1-2 h; After washing to neutral, immerse in a 3-7 wt% γ-aminopropyltriethoxysilane ethanol-water solution, and reflux at 80°C for 2-3 h; After taking out, dry at 100-110°C to obtain silane-modified carbon fiber with a surface grafting rate of ≥90%.

[0023] According to the embodiment of the present disclosure, the quartz sand has a particle size of 40-70 mesh, and the mass ratio of quartz sand to cement is 4.0-5.5:1.

[0024] According to the embodiment of the present disclosure, the expanding agent is light-burned MgO.

[0025] According to the embodiment of the present disclosure, the glass transition temperature Tg of the redispersible latex powder is 0-10°C, and the minimum film formation temperature is 0-5°C.

[0026] According to the embodiment of the present disclosure, the viscosity of the hydroxypropyl methyl cellulose ether is 40,000-60,000 mPa·s. The viscosity is measured by preparing a 2% aqueous solution and measuring the viscosity at 20°C.

[0027] In a second aspect, the present disclosure provides a method for preparing the dry-mixed thin anti-cracking waterproof plaster mortar of any one of the first aspect, comprising the following steps: Step a: dry-mixing cement, quartz sand, expanding agent, and hydroxypropyl methyl cellulose ether at 100-200 rpm for 2-3 min; Step b: adding silane-modified carbon fiber, redispersible latex powder, and nano-clay-alginic acid salt composite water-retaining system, and continuing to mix at <200 rpm for 3-5 min to avoid fiber damage; Step c: adding water according to a water-cement ratio of 0.18-0.22, and stirring for 3-5 min until uniform; Step d: placing and aging for 10-15 min before construction.

[0028] According to the embodiment of the present disclosure, low-speed mixing (<200 rpm) in step b can maintain the integrity of the fiber and avoid fiber breakage or damage during the mixing process, thereby maximizing the reinforcing effect of the fiber.

[0029] According to the embodiment of the present disclosure, the mixing temperature in step b is controlled at 15-30°C, and the relative humidity is 40-70%.

[0030] According to an embodiment of the present disclosure, the environmental humidity is kept greater than or equal to 60% and the temperature is kept between 5-35°C within 24 hours after the construction of step d.

[0031] The dry-mixed thin anti-cracking waterproof plaster mortar provided by the present disclosure has the following advantages: (1) The nano-clay-alginate composite water-retention system is introduced, a hydrogel network is formed by cross-linking sodium alginate with calcium ions, and a composite water-retention system is constructed by combining nano-attapulgite, thereby improving the water retention rate.

[0032] (2) The carbon fibers are modified by a silane coupling agent, the surface of the carbon fibers is modified by gamma-aminopropyl triethoxysilane, and the interfacial bonding strength with the thermal insulation board is improved.

[0033] (3) The cracking index is 0 mm, and the problem of micro-cracks is completely solved.

[0034] (4) The process is a full aqueous phase process, and VOC is zero-emission.

[0035] It should be understood that the above general description and the following detailed description are only exemplary and explanatory, and cannot limit the present disclosure. DETAILED DESCRIPTION

[0036] The present application will be further illustrated by the following examples, but it should be understood that these specific examples will not limit the scope of the present application in any way. It should be noted that, unless otherwise specified, the raw materials used in the following examples are commercially available.

[0037] Example 1: The raw materials are mixed in the following proportions by weight: cement 135 parts, 40-70 mesh quartz sand 600 parts, silane-modified carbon fiber 1.2 parts (gamma-aminopropyl triethoxysilane grafting rate 92%, length 6 mm), nano-attapulgite 6.0 parts, sodium alginate 2.0 parts, redispersible latex powder (Tg=5°C) 3.0 parts, hydroxypropyl methylcellulose ether (viscosity 50000 mPa·s) 0.3 parts, light burned MgO 7 parts.

[0038] Preparation steps: 1. Dry mix the cement, quartz sand, light burned MgO, and hydroxypropyl methylcellulose ether at a rotation speed of 150 rpm for 2 min; 2. Add the silane-modified carbon fiber, redispersible latex powder, and nano-clay-alginate composite (nano-attapulgite and sodium alginate are cross-linked by CaCl2 and then spray dried, with a particle size of 80 μm), continue to mix at a rotation speed of 180 rpm, a temperature of 25°C, and a humidity of 60% for 3-5 min; 3. Add water at a water-cement ratio of 0.20, stir for 5 min until uniform, and then stand for 15 min before construction.

[0039] Example 2: Raw material ratio, by weight: cement 140 parts, 40-70 mesh quartz sand 580 parts, silane-modified carbon fiber 1.0 parts (grafting rate of γ-aminopropyl triethoxysilane 90%, length 6 mm), nano-palygorskite 5.0 parts, sodium alginate 1.5 parts, re-dispersible latex powder (Tg = 3°C) 2.5 parts, hydroxypropyl methylcellulose ether (viscosity 45000 mPa·s) 0.4 parts, light burned MgO 8 parts.

[0040] Preparation steps are the same as Example 1.

[0041] Example 3: Raw material ratio, by weight: cement 150 parts, 40-70 mesh quartz sand 650 parts, silane-modified carbon fiber 0.8 parts (grafting rate of γ-aminopropyl triethoxysilane 91%, length 5.5 mm), nano-palygorskite 4.0 parts, sodium alginate 1.0 parts, re-dispersible latex powder (Tg = 8°C) 4.0 parts, hydroxypropyl methylcellulose ether (viscosity 40000 mPa·s) 0.1 parts, light burned MgO 10 parts.

[0042] Preparation steps are the same as Example 1.

[0043] Example 4: Raw material ratio, by weight: among them, the silane-modified carbon fiber is increased to 2 parts, and 3 mm, 6 mm, 9 mm carbon fiber is mixed at 1:2:1, and the rest of the components are the same as Example 1.

[0044] Preparation steps are the same as Example 1.

[0045] The construction area of Example 4 is a high stress area, such as the top and corner areas of the building, and the test bonding strength is 0.30 MPa, and the cracking index is 0 mm.

[0046] Comparative Example 1: The carbon fiber is not treated with silane, and the rest of the raw material ratio and preparation steps are the same as Example 1.

[0047] Comparative Example 2: The nano-clay-alginate composite is replaced with an equal amount of hydroxypropyl methylcellulose ether, and the rest of the raw material ratio and preparation steps are the same as Example 1.

[0048] Comparative Example 3: The raw material ratio is the same as Example 1, and the mixing speed in step 2 of the preparation steps is 400 rpm, and the rest of the steps are the same as Example 1.

[0049] Performance test method explanation: water retention rate: test the water retention performance of the mortar according to JGJ / T 70.

[0050] Tensile bonding strength: according to the provisions of 4.3.1 in DG / TJ 08-2433A-2023, the forming thickness is 3 mm, the test age is 14 d, the water resistance strength and freeze-thaw resistance strength are carried out according to the provisions of GB / T 29906, and the test age is 28 d.

[0051] Cracking index: according to T / SCIA 004-2024 Appendix A.

[0052] Water impermeability: according to Appendix C in JG / T 158, the test substrate is 5mm removable insulation formwork.

[0053] 2h Consistency loss rate: according to GB / T 25181, wherein the consistency testing instrument should be a Vicat apparatus in accordance with GB / T 1346. The standard consistency value range should be 45mm-50mm, and the mortar mixture should be no less than 300g.

[0054] 28d Compressive strength: according to JGJ / T 70.

[0055] Buckling ratio: according to GB / T 29906.

[0056] The test results of the above Examples 1-3 and Comparative Examples 1-3 are shown in the following table:

[0057] From the above, it can be seen that the water retention rate of Example 1 is 99.7% (Comparative Example 2 is only 90.2%), which confirms the high water locking capacity of the nanoclay-alginate composite system; the cracking index of all examples is 0 (Comparative Example 2 is 3.5mm), because the composite system forms a physical barrier to block the expansion of microcracks. The bonding strength of Example 1 to the insulation board (0.28MPa), and the failure occurs in the insulation layer; the strength of Comparative Example 1 (unmodified fiber) decreases by 35.7%, which proves that the silane coupling agent enhances the interfacial action through chemical bonding. Comparative Example 3 uses high-speed mixing, and the damage to the fiber leads to a decrease in compressive strength by 5.9%, and the cracking index increases to 0.4mm, highlighting the necessity of low-speed mixing (<200rpm) for maintaining the integrity of the fiber.

[0058] The above description is only for the preferred embodiments of the present disclosure and the explanation of the principles of the technology used. Those skilled in the art should understand that the scope of the invention involved in the present disclosure is not limited to the technical solutions formed by the specific combination of the above technical features, and should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with each other to form technical solutions with similar functions disclosed in the present disclosure (but not limited to).

Claims

1. A dry-mixed, thin-film, crack-resistant, and waterproof plastering mortar, characterized in that, By weight, it comprises: 120-150 parts cement; 550-650 parts of quartz sand; 0.8-2.4 parts of silane-modified carbon fiber, wherein the silane-modified carbon fiber is carbon fiber that has undergone surface grafting treatment with γ-aminopropyltriethoxysilane, and the grafting rate is ≥90%; 5-11 parts of nano-clay-alginate composite water-retaining system, wherein the composite water-retaining system is composed of sodium alginate and calcium ions cross-linked to form a hydrogel network and coated with nano-attapulgite, wherein sodium alginate is 1-3 parts and nano-attapulgite is 4-8 parts. 2-4 parts of redispersible latex powder; Hydroxypropyl methylcellulose ether, 0.1-0.5 parts; 5-10 parts of expanding agent.

2. The dry-mixed thin-film crack-resistant and waterproof plastering mortar according to claim 1, characterized in that, The nano-clay-alginate composite water-retaining system is prepared through the following steps: Nano-attapulgite clay is dispersed in deionized water to form a 5-10 wt% suspension; Sodium alginate was added at 25±5℃ and 200-400 rpm with stirring to achieve a sodium alginate concentration of 1-3 wt%. Slowly add 2-3 wt% CaCl2 solution to carry out ionic cross-linking; After cross-linking, spray drying is performed to obtain microspheres with a particle size of 50-100 μm.

3. The dry-mixed thin-film crack-resistant and waterproof plastering mortar according to claim 1, characterized in that, The preparation method of the silane-modified carbon fiber includes: The carbon fiber was placed in a mixture of concentrated sulfuric acid and concentrated nitric acid (volume ratio 3:1) and acid-washed at 60-80℃ for 1-2 hours. After washing with water until neutral, immerse in 3-7 wt% γ-aminopropyltriethoxysilane in an ethanol-water solution and reflux at 80°C for 2-3 h. After removal, the carbon fibers are dried at 100-110℃ to obtain silane-modified carbon fibers with a surface grafting rate of ≥90%.

4. The dry-mixed thin-film crack-resistant and waterproof plastering mortar according to claim 1, characterized in that, The quartz sand has a particle size of 40-70 mesh, and the mass ratio of quartz sand to cement is 4.0-5.5:

1.

5. The dry-mixed thin-film crack-resistant and waterproof plastering mortar according to claim 1, characterized in that, The expanding agent is lightly calcined MgO.

6. The dry-mixed thin-film crack-resistant and waterproof plastering mortar according to claim 1, characterized in that, The glass transition temperature (Tg) of the redispersible latex powder is 0-10℃, and the minimum film-forming temperature is 0-5℃.

7. The dry-mixed thin-film crack-resistant and waterproof plastering mortar according to claim 1, characterized in that, The viscosity of the hydroxypropyl methylcellulose ether is 40,000-60,000 mPa·s.

8. A method for preparing the dry-mixed thin-film crack-resistant and waterproof plastering mortar according to any one of claims 1-7, characterized in that, Includes the following steps: Step a: Dry mix cement, quartz sand, expanding agent, and hydroxypropyl methylcellulose ether at 100-200 rpm for 2-3 min; Step b: Add silane-modified carbon fiber, redispersible latex powder and nano-clay-alginate composite water-retaining system, and continue mixing at <200 rpm for 3-5 min to avoid fiber damage; Step c: Add water at a water-cement ratio of 0.18-0.22 and stir for 3-5 minutes until homogeneous; Step d: Allow to stand for 10-15 minutes before proceeding with the application.

9. The method according to claim 8, characterized in that, In step b, the mixing temperature is controlled at 15-30℃ and the relative humidity is 40-70%.

10. The method according to claim 8, characterized in that, After step d, maintain an ambient humidity of ≥60% and a temperature of 5-35℃ for 24 hours.

Citation Information

Patent Citations

  • Heat preserving crack resistant mortar for exterior wall

    CN101195529A

  • Preparation method of modified fibers having high interface binding strength with cement-based material

    CN106977126A

  • Soilless spray-seeding substrate for mine greening and preparation method of soilless spray-seeding substrate

    CN114467680A

  • Low-cost mine filling material and preparation method thereof

    CN119683923A

  • Water-preserving agent for preventing water leakage of dry or semi-dry farmland

    CN1243858A

Cited By

  • Environment-friendly anti-cracking dry-mixed mortar as well as preparation method and application thereof

    CN122233717A